2018
DOI: 10.3389/fnmol.2018.00226
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Alterations of Ionotropic Glutamate Receptors in the Hippocampus of the Ts65Dn Mouse Model of Down Syndrome

Abstract: Down syndrome (DS), the main genetic cause of intellectual disability, is associated with an imbalance of excitatory/inhibitory neurotransmitter systems. The phenotypic assessment and pharmacotherapy interventions in DS murine models strongly pointed out glutamatergic neurotransmission alterations (specially affecting ionotropic glutamate receptors [iGluRs]) that might contribute to DS pathophysiology, which is in agreement with DS condition. iGluRs play a critical role in fast-mediated excitatory transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
(74 reference statements)
2
8
0
Order By: Relevance
“…NMDAR stimulation simultaneously activates phosphatases and phosphoproteomic studies showed that LTP causes similar numbers of sites to be phosphorylated and dephosphorylated (Li et al., 2016). The regulated phospho‐sites are span receptors, scaffolding proteins and transcription factors, and thus reorganize both the synaptic structure and downstream signalling (Coba, 2019) and may be dysregulated in neurological disorders (Gómez de Salazar, Grau, Ciruela, & Altafaj, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NMDAR stimulation simultaneously activates phosphatases and phosphoproteomic studies showed that LTP causes similar numbers of sites to be phosphorylated and dephosphorylated (Li et al., 2016). The regulated phospho‐sites are span receptors, scaffolding proteins and transcription factors, and thus reorganize both the synaptic structure and downstream signalling (Coba, 2019) and may be dysregulated in neurological disorders (Gómez de Salazar, Grau, Ciruela, & Altafaj, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3381, Cell Signaling Technology, Danvers, MA, USA) (Gomez de Salazar et al . ), a rabbit anti‐phospho‐GluN1 Ser 896 antibody (1:500, no. ABN88, EMD Millipore; Billerica, MA, USA) (Xie et al .…”
Section: Methodsmentioning
confidence: 99%
“…Postmortem EC from human subjects was selected for our study because EC in the medial temporal lobe is already affected in the early stages of AD (Braak and Braak, 1991). The cortical subsynaptic fractionation protocol was previously validated by our group by western blotting using specific subsynaptic compartment markers (Gomez de Salazar et al, 2018).…”
Section: Postsynaptic Proteomic Signature Of the Ts65dn Mice And Post...mentioning
confidence: 99%
“…However, this study found only modest changes in the levels of synaptic proteins in the Ts65Dn mouse model. Therefore, we used proteomic analyses to study the postsynaptic and extrasynaptic fractions of the hippocampus of Ts65Dn mice (Gómez de Salazar et al, 2018) to avoid the confounding effect of mixing different brain regions.…”
Section: Introductionmentioning
confidence: 99%